TARIXIY-MADANIY MEROSLARIMIZNING TA’LIM-TARBIYAVIY VA AXLOQIY MANBALARI - Bekbosinov, D.A. (SCIENCE and SOCIETY, 2024)
The article deals with the educational and moral sources of our historical and cultural heritage, the analysis of material culture found in historical monuments, the issues of using the important recommendations and options related to the teaching of professions and trades to young people in the works of great scholars in today’s education and training process.
Keywords: educational; moral traditions; craft centers and workshops; "enterprise"; "workshop"; a group or partnership of artisans with highly specialized craftsmen; brochure (charter) of artisans; "ulfagar"